2017
DOI: 10.1038/s41598-017-03388-3
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition-sarcopenia syndrome predicts mortality in hospitalized older patients

Abstract: A new term, malnutrition-sarcopenia syndrome (MSS), was recently coined to describe the clinical presentation of both malnutrition and sarcopenia. The aim of this study was to investigate the association between MSS and long-term mortality in older inpatients. We conducted a prospective study in acute geriatric wards of two local hospitals in China. Muscle mass and malnutrition were estimated by anthropometric measures and the Mini Nutritional Assessment (MNA). Of the 453 participants, 14 (3.1%) had sarcopenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
91
2
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(110 citation statements)
references
References 32 publications
8
91
2
9
Order By: Relevance
“…The 'Low SPPB-scores' group have a fifty percent higher risk compared to the 'High SPPB-scores' group. These data of hospitalized geriatric patients confirm the results of other studies in different populations 4,10,13,15,[21][22][23] . Figure 1 gives an overview of the Kaplan Meier curves of all these significant class variables.…”
Section: Discussionsupporting
confidence: 82%
“…The 'Low SPPB-scores' group have a fifty percent higher risk compared to the 'High SPPB-scores' group. These data of hospitalized geriatric patients confirm the results of other studies in different populations 4,10,13,15,[21][22][23] . Figure 1 gives an overview of the Kaplan Meier curves of all these significant class variables.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, among male residents in a nursing home, MNA scores were significantly lower in residents having low compared with having normal skeletal muscle mass (17.1 ± 3.4 vs 19.6 ± 2.5; P = .005) . More importantly, in a prospective study, subjects with malnutrition risk and sarcopenia have a risk for mortality 4 times higher than subjects without sarcopenia with normal nutrition . Therefore, Vandewoude et al recently indicated the MSS to depict the clinical scenario characterized by both malnutrition and sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed earlier, malnutrition and sarcopenia are conditions frequently found in older adults that lead to negative outcomes including increased morbidity and mortality and increased healthcare costs and rehospitalizations . Usually, these conditions have been separately screened, but rarely are both conditions simultaneously assessed .…”
Section: Discussionmentioning
confidence: 99%
“…8 This syndrome was recently pointed out as a prognostic indicator for long-term mortality in hospitalised older patients. 9 Sarcopenia and undernutrition are both associated with higher care costs 10,11 and several adverse health outcomes, namely poor quality of life, 12,13 prolonged length of stay in hospital 11,14,15 and mortality. 11,16,17 Routine undernutrition identification is increasing in the clinical practice, but sarcopenia remains poorly identified.…”
Section: Introductionmentioning
confidence: 99%